Pengabdian Kepada Masyarakat dalam Rangka Pemulihan Dapur Keluarga Korban Bencana Cianjur di KP. Seuseupan RT. 05 RW. 01 Desa Wangunjaya Kec. Cugenang - Levyda Levyda; Giyatmi Giyatmi; Ani Siska MY (Cv. Utility Project Solution, 2023)
Monday, November 21, 2022 an earthquake occurred in the Cianjur area with a magnitude of Mw 5.6 which affected all aspects, one of which was the economic aspect. One of the affected villages is Kp. Seuseupan RT. 05 RW. 01 Desa Wangunjaya Kecamatan Cugenang. The impact of the earthquake, especially in causing damage to kitchen equipment. The damage disrupts the function of family food procurement. This community services aims to support the restoration of kitchen functions. One form of Tridharma that is caried out is Community Service. The target of this PKM is to divide kitchen equipment consisting of 1 bucket, 1 pot or pan & silk, 1 can of sweetened condensed milk, sanitary napkins and 1 lunch box for 130 heads of household, and 1 tarpaulin for RT 05 rw 01 Kp Seuseupan Wangunjaya Village district Cugenang. The distribution was carried out by residents and led by the head of the RT. This Community Service encourages the independence of families of victims of the Cianjur disaster in providing family consumption. Cooking utensils can also be used to start small businesses such as selling food and drink thereby increasing family income. The implementation method is by first collecting data and distributing aid directly as well as counseling to mothers who are victims of the disaster. Community Service runs smoothly and the distribution and counseling provided are in accordance with the data held at the time of data collection.